2020
DOI: 10.1021/acs.jmedchem.0c00910
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GiardiaDrug Discovery: Current Status and Gut Feelings

Abstract: Giardia parasites are ubiquitous protozoans of global importance that impact a wide range of animals including humans. They are the most common enteric pathogen of cats and dogs in developed countries and infect ∼1 billion people worldwide. While Giardia infections can be asymptomatic, they often result in severe and chronic diseases. There is also mounting evidence that they are linked to postinfection disorders. Despite growing evidence of the widespread morbidity associated with Giardia infections, current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 196 publications
0
45
0
1
Order By: Relevance
“…The screening for new giardicidal drugs is undoubtedly a priority, since drug resistance and treatment failures are increasing [22]. As GlADI is absent in the human host, this enzyme is an attractive target for drug design against giardiasis [23].…”
Section: Discussionmentioning
confidence: 99%
“…The screening for new giardicidal drugs is undoubtedly a priority, since drug resistance and treatment failures are increasing [22]. As GlADI is absent in the human host, this enzyme is an attractive target for drug design against giardiasis [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several compounds have been tested against Giardia infections in dogs as benzimidazoles, in particular fenbendazole, and metronidazole that poses activity against the parasite (23)(24)(25)(26)(27)(28). Other studies reported the efficacy of ronidazole, nitazoxanide, azithromycin, tinidazole, and ipronidazole and other drugs such as quinacrine, furazolidone, in reducing Giardia cysts shed by infected dogs (17,(29)(30)(31)(32). Another option recommended by the European Scientific Counsel Companion Animal Parasites (ESCAAP) is the combination of febantel (a prodrug metabolized in vivo to fenbendazole)/pyrantel/praziquantel at the standard deworming dose (15.0 mg/kg of febantel, 14.4 mg/kg pyrantel, 5.0 mg/kg praziquantel) repeated once daily for 3 days (33).…”
Section: Introductionmentioning
confidence: 99%
“…Last not least, next to the development and implementation of new therapeutic strategies, infection prevention should not be neglected. Therefore, studies on successful enforcement of adequate hygiene standards to reduce both the transmission of G. duodenalis and the infectious burden will remain an issue of relevance [ 169 ]. Further, due to the difficult-to-control resistance conditions including the risk of multidrug resistance in G. duodenalis [ 170 ], also vaccine development remains an ongoing issue for the control of giardiasis [ 171 ].…”
Section: Discussionmentioning
confidence: 99%